Stellar kinematics, morphology and local environment of galaxies with integral field spectroscopy - Graham, MT (2019)
In this thesis, I study the stellar angular momentum within one effective radius, λRe of a few thousand galaxies and consider how this property relates to other galaxy properties such as stellar mass, optical morphology and environment. I make use of data from the Sloan Digital Sky Survey's (SDSS) Mapping Nearby Galaxies at Apache Point Observatory (MaNGA) survey which is a large integral field spectroscopic survey. I classify early-type galaxies (ETGs) as slow rotators if λRe < 0.08 + 0.25ϵ and ϵ < 0.4, where ϵ is the galaxy flattening, and as fast rotators if otherwise. I present the (λRe,ϵ) diagram for about 2300 galaxies and provide the first conclusive evidence that fast and slow rotator ETGs form a bimodality in angular momentum suggesting that they are kinematically distinct populations. I show that they also form a bimodality in other properties such as stellar mass and kinematic morphology, which I attribute as being a direct consequence of the existence of two ETG formation channels, a gas rich (wet) accretion channel which produces FRs and a gas poor (dry) merger channel which produces SRs.